Culturally Responsive Game-Based Learning: Integrating PjBL to Enhance Students' Understanding of Linear Equations - Sasna Pratiwi; Moh. Mahfud Effendi; Siti Khoiruli Ummah; Zulkifley Mohamed (FKIP Universitas Lampung, 2026)
This study aims to develop and evaluate PjBL-based educational games that integrate mathematics learning with local culture in senior high schools, specifically a game called